2021
DOI: 10.1016/j.chemosphere.2020.127978
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on air quality in Chandigarh, India: Understanding the emission sources during controlled anthropogenic activities

Abstract: The variation in ambient air quality during COVID-19 lockdown was studied in Chandigarh, located in the Indo-Gangetic plain of India. Total 14 air pollutants, including particulate matter (PM 10 , PM 2.5 ), trace gases (NO 2 , NO, NO x , SO 2 , O 3 , NH 3 , CO) and VOC’s (benzene, toluene, o-xylene, m,p-xylene, ethylbenzene) were examined along with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 57 publications
5
120
1
1
Order By: Relevance
“…During the lockdown period, this work and other recent studies highlighted the impact of restricted anthropogenic activities on air quality across India and other parts of the world (Sharma et al 2020;Jain and Sharma 2020;Mahato et al 2020;Dantas et al 2020;Chauhan and Singh 2020;Mor et al 2020). In India, particulate matter (PM 2.5 and PM 10 ) and NO 2 show a significant reduction of up to 40-50% in the many megacities during the lockdown period as highlighted by Jain and Sharma (2020), Mahato et al (2020), Singh et al (2020a), and Biswal et al (2020).…”
Section: Air Quality In Lockdown and Implication For Better Air Qualitysupporting
confidence: 50%
See 1 more Smart Citation
“…During the lockdown period, this work and other recent studies highlighted the impact of restricted anthropogenic activities on air quality across India and other parts of the world (Sharma et al 2020;Jain and Sharma 2020;Mahato et al 2020;Dantas et al 2020;Chauhan and Singh 2020;Mor et al 2020). In India, particulate matter (PM 2.5 and PM 10 ) and NO 2 show a significant reduction of up to 40-50% in the many megacities during the lockdown period as highlighted by Jain and Sharma (2020), Mahato et al (2020), Singh et al (2020a), and Biswal et al (2020).…”
Section: Air Quality In Lockdown and Implication For Better Air Qualitysupporting
confidence: 50%
“…The various lockdown phases have a difference in restrictions resulting in variation in PM 2.5 levels in different stages of lockdown. In the first phase of lockdown, all human activities were halted except for emergency services (Singh et al 2020a;Mor et al 2020). After that, in consecutive phases, increased activities, like movements of people stuck in lockdown, relaxation in timings to buy market goods, and the opening of essential industries, were allowed with limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding Gerena, the mine zone showed an increase of +67.9% in SO 2 in comparison with a decrease of -24.2% in NO 2 . All these extreme increases in SO 2 levels must be attributed to the increase in burning of coal [ 39 ] or other fossil fuels by thermal power plants [ 40 ] or other industrial activities, such as mines or re neries. According Wang et al [25], concentrations of SO 2 and other pollutants such as CO and NO 2 appeared to have positive effect on hospitalizations, especially at high concentrations, for instance by bronchiectasis.…”
Section: Sulfur Dioxide and Hydrogen Sul Dementioning
confidence: 99%
“…Increase in the concentration levels of trace gases and particulate matter has been a challenging environmental issue in urban and industrial areas.Numerous studies have been attempted across the globe to understand the air pollution concentrations during lockdown period and results indicate varied range of percentage reductions in pollutant concentrations. These studies are based on ground based measurements alone (Mohato and Ghosh, 2020;Mor et al, 2020) or satellite data alone (Biswal et al, 2020a;Xu et al, 2020) orwith a combinationof ground and satellite (Ratnam et al, 2020;Biswal et al, 2020b;Singh and Chauhan, 2020). Biswal et al (2020aBiswal et al ( & 2020b reported lockdown induced changes in tropospheric NO2 variability over the urban and rural regions of Indian sub-continent with marked reduction of 30-50 % over https://doi.org/10.5194/acp-2020-1227 Preprint.…”
Section: Introductionmentioning
confidence: 99%